Redesign of Museum Installations with Interactive and Sensorial Experience Approach - Wiradarmo, Aulia Ardista; Huwaida, Nisrina Fairuz; Miranda, Asyura; Lim, Karen Bianca; Gayatri, Ni Luh Putu Ananda (Desainpedia: Jurnal Desain Produk dan Desain Komunikasi Visual, 2024)
In the past decades, museums continued to be demanded to surpass their primary function as a place for archival and historical artifact conservation to be a medium for knowledge dissemination as well as recreation. The “do not touch” slogan that is often placed on the typical museum glass box is considered no longer relevant when museums must satisfy visitors’ desires instead of solely focusing on objects. The aim of this research is to answer the challenge by integrating technology in redesigning conventional museum installations. The utilised methodologies are literature review and case study to develop new products. It integrates theories related to interaction and sensory experience into a design framework which includes types of experience, types of attraction, modes of apprehension, and five senses. Sherlock Holmes Museum is chosen as a case study with four installation redesigns as the final outcomes, namely: (1) Holmes Loop, (2) Holmes Guide, (3) Holmes POV, and (4) Holmes Puzzle. The generated installation concepts prove that product design has an essential role in cultural innovation so that museums continue to be relevant in between technological advancement. On the other hand, the design framework succeeds in helping idea generation process, thus it can be used as a reference to develop installations in other museums.